A text-critical analysis of the Lamentations manuscripts from Qumran (3QLam, 4QLam, 5QLama and 5QLamb): establishing the content of an Old Testament book according to its textual witnesses among the Dead Sea scrolls - Kotzé, Gideon (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh (Old and New Testament))--Stellenbosch University, 2011.